Revisit of hydrothermal plumes along 63°- 64°E of Carlsberg Ridge: A comprehensive survey to assess physicochemical features of non-buoyant plumes - Lina L. Fernandes; Durbar Ray; S. Gautham; V.P. Akhil; Robin John; V. Yatheesh (Journal of Marine Systems, 2026)

Comparative genomics analysis of aneuploidy and cellular fragmentation dynamics in mammalian embryos - R. Tippner-Hedges; J. Budrewicz; E.S. Rubin; K. Ray; B.A. Davis; M. Okovat; L. Carbone; E.S. Metcalf; S.L. Chavez (Journal of Equine Veterinary Science, 2026)

Corrigendum to “Positive feedback of forest cover in maintaining hydrological equilibrium under recent climate change projections and land use change scenarios” [J. Atmos. Sol. Terr. Phys. 285 (2026) 106880] - Nirmal Kumar; Amit Dubey; Szilárd Szabó; José Francisco de Oliveira Júnior; Sudhir Kumar Singh; László Bertalan; Ram Avtar; Ram L. Ray (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Positive feedback of forest cover in maintaining hydrological equilibrium under recent climate change projections and land use change scenarios - Nirmal Kumar; Amit Kumar Dubey; Szilárd Szabó; José Francisco de Oliveira Júnior; Sudhir Kumar Singh; László Bertalan; Ram Avtar; Ram L. Ray (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Little difference in the carbon balance of ryegrass/white clover- and plantain-dominated swards under dairy grazing - A. M. Wall; D. I. Campbell; S. Ray; J. P. Goodrich; L. A. Schipper (Nutrient Cycling in Agroecosystems, 2026)
Incorporating plantain into grazed pasture swards is proposed as an approach to reduce nitrate leaching and nitrous oxide emissions. However, consideration must be given to potential emission-swapping, such as a reduction in soil carbon (C), which can contribute to increases in atmospheric CO 2 . We compared the net ecosystem C balance (NECB) of two adjacent newly-sown paddocks (~ 3 ha each) of (i) traditional ryegrass and white clover pasture (RyWC) and (ii) a pure plantain sward, to assess whether plantain was beneficial or detrimental for the carbon balance. The NECB was calculated by combining eddy covariance (EC) measurements of CO 2 with measurements and estimates of lateral C transfers. Concurrently, regular measurements of sward composition and properties were taken. During the approximately 2.5-year experiment, the RyWC sward had an NECB of −199 g C m −2 period −1 compared with −273 g C m −2 period −1 for the plantain sward. The slightly larger loss from the plantain sward was attributed to lower excretal C returns due to differences in grazing duration (13.9 days for the RyWC paddock, and 5.9 days for the plantain paddock) during the first year of grazing. In the second year, the grazing management of the two paddocks was the same, and the NECBs were comparable. Both pasture dry matter production and CO 2 uptake were similar between the swards, although the lower C content of the plantain resulted in smaller C exports by either harvest or grazing. We conclude that small differences in NECB (and assumed soil C) between a pure plantain sward and a traditional ryegrass and white clover sward are associated with management rather than pasture species.

Rainfall Dynamics in Sri Lanka Over Five Decades (1970–2023): Implications for Agricultural Adaptation to Climate Change - N. S. Abeysingha; S. D. Madurapperuma Arachchige; M. S. V. Pathirana; Ram L. Ray (International Journal of Climatology, 2026)
Climate change is affecting agricultural productivity and economic stability across many parts of the world, but small islands like Sri Lanka are more vulnerable to the effects of climate change. As a result, assessing recent rainfall dynamics is crucial for developing effective climate adaptation measures. This study analysed rainfall data from 44 meteorological stations across Sri Lanka's dry, wet and intermediate climatic zones spanning 54 years (1970–2023) to evaluate rainfall dynamics. The analysis employed multiple statistical methods, including the coefficient of variation (CV), Precipitation Concentration Index (PCI), Standardized Precipitation Index (SPI), Mann–Kendall (MK) test with Sen's slope estimator and innovative trend analysis (ITA). Results revealed increasing annual rainfall trends at 79.5% of stations, with 40% showing statistically significant increases ( p p

Assessing the impact of hurricanes on the carbon cycle using SMAP satellite and in-situ observations: Role of land cover and precipitation - Ram L. Ray; Nirmal Kumar; Sanjita Gurau; Ali Raza; Nawab Khan; Sudhir Kumar Singh; Esther Tosin Kayode; Yiping He (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Assessing spatiotemporal land dynamics using Google Earth Engine and random forest: trends and drivers of change in Ethiopia’s fragile Jema River Basin - Tamrat Selamu; Sileshi Degefa; Wakgari Furi; Tegegne Molla Sitotaw; Ram L. Ray (Environmental Monitoring and Assessment, 2026)

Melanin and methylation: coat color is linked to directional epigenetic shifts in Alaskan wolves - Elizabeth L. Sheldon; Gretchen H. Roffler; M. E. Lauer; Daniella Ray; Danielle Dawkins; Matthew Stephen Broderick; Aaron W. Schrey (Mammal Research, 2026)

Complex eruption processes and deposits of basaltic fissures: insights from the ~37 ka Budj Bim volcanic complex, Southeastern Australia - Janine L. Kavanagh; Katy J. Chamberlain; Jade A. Hrintchuk; Elisabetta Mariani; Julie Boyce; Stefano Urbani; Tegan A. Havard; Kate M. Williams; Ray A. F. Cas (Bulletin of Volcanology, 2026)
Throughout Earth’s history, eruptions from volcanic fissures have been responsible for some of the largest outpourings of basaltic magma, impacting climate and society. In continental monogenetic settings, these eruptions can occur on short timescales and with short notice after long quiescence. Their deposits are often quickly destroyed or buried as the eruption progresses, limiting understanding of eruption triggers and hazards uniquely garnered from these tephra layers and lavas. The ~37 ka Budj Bim Volcanic Complex (BBVC) in the active intracontinental monogenetic Newer Volcanics Province (NVP), southeastern Australia (~4.5 Ma to present), is a rarely preserved volcanic fissure system that provides new insight on how magma ascent dynamics impact eruptions. The BBVC comprises a 2.2 km long array of basaltic scoria cones, spatter cones, an elongate open crater with steep inward-sloping walls and a substantial lava-tube-fed flow field. Newly logged eruption sequences, petrography and geochemical analysis reveal five eruption stages, involving vent-shifting along a dyke-fed fissure, and rapid changes in eruption styles between Strombolian and micro-Plinian activity interspersed with concurrent and intermittent phreatomagmatism. The eruption culminated in the establishment and then breach of an elongate lava lake, feeding the > 30 km long culturally significant Tyrendarra lava flow (UNESCO World Heritage site). The BBVC eruption would have evolved similarly to the 2014–2015 Bárðarbunga-Holuhraun fissure eruption in Iceland, but with increased complexity due to its intraplate continental setting and feeder dyke interaction with aquifers and near-surface faults, resulting in greater level of phreatomagmatism and explosion depths potentially down to 320 m. This finding must be considered to improve future eruption scenario assessments in the NVP and builds new understanding of complex volcanic fissure eruption behaviour that can be applied to similar systems around the world.

Recent hydroclimatic extremes in the Cypress Creek watershed, Texas, USA - N S Abeysingha; Ram L Ray (Journal of Earth System Science, 2026)

Predicting the distribution of the invasive charru mussel (Mytella strigata) in estuarine environments - Gency L. Guirhem-Helican; John Ray N. Moleño; Irvin Michael M. Palmos; Harold M. Monteclaro (Estuarine, Coastal and Shelf Science, 2026)

Snow cover analysis using NDSI and SWI indices in Pindari-Kafni Glacier valleys, Kumaon Himalaya - Pankaj Chauhan; Ram L. Ray; Supriti Samanta; Dharmaveer Singh; Rajib Shaw; Nirmal Kumar (Applied Geomatics, 2026)

Global dynamics of climate smart agricultural practices and technologies: Recent advancements, challenges and potential future pathways - A review - Belay Tizazu Mengistie; Ram L. Ray (Agricultural Systems, 2026)

Manistee, a new Round-White Early to Mid-Season Maturing Potato Variety with Excellent Long-Term Storage Potential - David S. Douches; Joseph J. Coombs; William L. Behling; Ray Hammerschmidt; Greg E. Steere; Matthew L. Zuehlke; Christopher M. Long (American Journal of Potato Research, 2025)
Manistee is a round white chip-processing potato ( Solanum tuberosum ) variety developed for long-term storage. Evaluated as MSL292-A, Manistee is a selection from a cross between Snowden and the chip-processing breeding line MSH098-2. The tubers of Manistee are compressed, round with shallow eyes and early to mid-season maturity. Field testing and on-farm trials show that this variety has high yield potential with specific gravity comparable to Snowden and similar to better tolerance to blackspot bruise. Manistee was formally released in 2013 and has demonstrated reliable and excellent long-term storage chip-processing quality up to eight months post-harvest which extends the chip-processing storage season beyond Snowden. Furthermore, preliminary studies with Manistee, Snowden, Lamoka and Pike tuber disks demonstrated that Manistee started the wound healing process faster than Lamoka and Pike and slightly faster than Snowden which supports observations of stable and reliable commercial storage of the tubers for chip-processing.

The teat skin microbiota of organic primiparous dairy cows is dynamic during the transition period - C.J. Dean; T. Ray; F. Peña-Mosca; T.J. Wehri; K. Sharpe; A.M. Antunes; E. Doster; L. Fernandes; V.F. Calles; C. Bauman; B. Heins; P. Pinedo; et al. (Preventive Veterinary Medicine, 2025)

Fate, distribution, and transport dynamics of indium in a polymetallic mine waste environment: An integrated mineralogical characterisation and geochemical modelling study - Olivia Mejías; Thomas Poulet; Pouria Behnoudfar; Laura Jackson; Justin Freeman; Thomas Ray Jones; Daryl L. Howard; Anita Parbhakar-Fox (Science of The Total Environment, 2025)

Future hydro-climate extremes in the cypress creek watershed in Texas under different CMIP6 scenarios - N. S. Abeysingha; Ram L. Ray; Temesgen Gashaw Tarkegn (Sustainable Water Resources Management, 2025)

Potential of algae as fertilizers and plant stimulants for sustainable and eco-friendly agriculture - Anh Quynh Nguyen; Abdul Latif Khan; Ram L. Ray; Shan Xiaonan; Venkatesh Balan (Algal Research, 2025)

Enhancing plant and soil health through organic amendments in a humid environment - Ram L. Ray; Kusalika M. Kularathna; Richard W. Griffin; Nimal Abeysingha; Selamawit Woldesenbet; Almoutaz Elhassan; Ripendra Awal; Ali Fares (Rhizosphere, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Simultaneous Drought and Heatwave Events During Austral Summer in Northeast Brazil - Katyelle F. S. Bezerra; Helber B. Gomes; Hakki Baltaci; Pallav Ray; Janaíına P. Nascimento; Dirceu L. Herdies; Matheus J. A. Lyra; Maria Cristina L. Silva; Fabrício D. S. Silva; Cláudio M. Santos e Silva; Heliofábio B. Gomes (International Journal of Climatology, 2025)
The simultaneous occurrence of heatwaves and droughts is becoming more frequent and intense under climate change, particularly affecting vulnerable regions like Northeast Brazil (NEB). This study presents a comprehensive assessment of these compound extremes using long‐term in situ observations and ERA5 reanalysis. Heatwaves were defined by daily temperatures exceeding the 90th percentile, and droughts by the standardised precipitation index (SPI‐1). Results reveal substantial spatio‐temporal variability in these events, with sharp increases in frequency, duration, and intensity since the early 1990s–especially in 1998, 2006 and 2015, linked to La Niña and El Niño events. Atmospheric analyses showed positive temperature anomalies at 2 m, persistent negative specific humidity at multiple pressure levels, and contrasting circulation anomalies: positive flow at 850 hPa, negative at 500 hPa, and changes in divergence and vorticity. The semiarid region of the northeast was the most affected by drought, while the northeastern coast had higher frequencies of heatwaves, with longer durations. These findings highlight the complex interactions driving compound extremes in NEB and underscore the urgent need for regional adaptation and mitigation strategies.

Corrigendum to “Multiple-species resistance to avermectin/milbemycin anthelmintics on beef cattle farms in Georgia, USA” [Vet. Parasitol. 336 (2025) 110435] - Leonor Sicalo Gianechini; Kelsey L. Paras; Melissa M. George; Sue B. Howell; Bob Storey; Matthew J. Denwood; Ray M. Kaplan (Veterinary Parasitology, 2025)

Surface water quality under climate change scenarios in the Bosque watershed, Central Texas of United States - Gebrekidan Worku Tefera; Ram L. Ray; Vijay P. Singh (Ecohydrology & Hydrobiology, 2025)

Multiple-species resistance to avermectin anthelmintics on beef cattle farms in Georgia, USA - Leonor Sicalo Gianchini; Kelsey L. Paras; Melissa M. George; Sue B. Howell; Bob Storey; Matthew J. Denwood; Ray M. Kaplan (Veterinary Parasitology, 2025)

Efficacy of unbaited and baited green multi-funnel traps for detection of Agrilus species and other wood-boring beetle taxa - Giacomo Santoiemma; Jon Sweeney; Everett G. Booth; Giacomo Cavaletto; Gianfranco Curletti; Sarah M. Devine; Joseph A. Francese; Emily K. L. Franzen; Filippo Giannone; Mischa Giasson; Jerzy M. Gutowski; Cory Hughes; et al. (Journal of Pest Science, 2025)
Semiochemical-baited traps are a key component of post-border surveillance for detection of non-native and potentially invasive bark and wood-boring beetles (Buprestidae, Cerambycidae, Curculionidae: Scolytinae) at risk of introduction in untreated woody materials used in global trade. Because the particular species that may arrive with imported goods is unknown, plant protection agencies need trapping protocols that effectively survey all three taxa. Baiting traps with host volatiles and aggregation/sex pheromones of longhorn beetles increases efficacy of detecting Cerambycidae and Scolytinae, but its effect on detection of Agrilus species and other jewel beetles is unknown. In this multi-country trapping study we found that the addition of ethanol and common aggregation/sex pheromones of longhorn beetles to green multi-funnel traps placed in the mid-upper forest canopy had negative effects on abundance of Agrilus species and other jewel beetles collected but no effect on their species richness, and significant positive effects on species richness and abundance of Cerambycidae and Scolytinae. Baiting green canopy traps with longhorn beetle pheromones increased the efficacy of traps for detecting total target taxa of bark and wood-boring beetles at risk of international movement in untreated woody materials. This information is beneficial for the design of multi-taxa surveys, potentially saving money and resources without decreasing trapping efficacy.

Equine welfare assessment skills certification course - R. Stewart; B. Wassel; A. Best; L. Ray; B. McGonagill; B. Jackson; P. Sapp; K. Duberstein (Journal of Equine Veterinary Science, 2025)

Mitigating greenhouse gas emissions in a cotton production system using various management practices - Hossein Sahabi; Rooholla Moradi; Ram L. Ray; Amir Hossein Saeidnejad (Journal of Environmental Chemical Engineering, 2025)

Effects of Disturbance and Fertilisation on Plant Community Synchrony, Biodiversity and Stability Through Succession - Janette L. Davidson; Kaitlyn R. McKnight; Megan Szojka; Dustin Gannon; Nathan I. Wisnoski; Chhaya M. Werner; Maowei Liang; Eric W. Seabloom; Courtenay Ray; Melissa H. DeSiervo; Lauren G. Shoemaker (Ecology Letters, 2025)
Global change drivers alter multiple components of community composition, with cascading impacts on ecosystem stability. However, it remains largely unknown how interactions among global change drivers will alter community synchrony, especially across successional timescales. We analysed a 22‐year time series of grassland community data from Cedar Creek, USA, to examine the joint effects of pulse soil disturbance and press nitrogen addition on community synchrony, richness, evenness and stability during transient and post‐transient periods of succession. Using multiple regression and structural equation modelling, we found that nitrogen addition and soil disturbance decreased both synchrony and stability, thereby weakening the negative synchrony–stability relationship. We found evidence of the portfolio effect during transience, but once communities settled on a restructured state post‐transience, diversity no longer influenced the synchrony–stability relationship. Differences between transient and post‐transient drivers of synchrony and stability underscore the need for long‐term data to inform ecosystem management under ongoing global change.

Comparing voluntary and government-mandated management measures for meeting sustainable fishing targets - Michael C. Melnychuk; Samantha Lees; Pedro Veiga; Jennifer Rasal; Nicole Baker; Lauren Koerner; Daniel Hively; Hiroyuki Kurota; Carryn L. de Moor; Maite Pons; Pamela M. Mace; Ana M. Parma; et al. (Journal of Environmental Management, 2025)

Life history strategies determine response to SRT driven crash in anammox bioreactors - Christian A. White; Edmund H. Antell; Sarah L. Schwartz; Jennifer E. Lawrence; Ray Keren; Lijie Zhou; Ke Yu; Wei-Qin Zhuang; Lisa Alvarez-Cohen (Water Research, 2025)

Seasonal nutrient loadings in four monsoonal micro/meso tidal tropical estuaries, west coast of India - Lina L. Fernandes; Pratima M. Kessarkar; Jayu Narvekar; Durbar Ray (Marine Environmental Research, 2025)

Evaluation of easterly wave disturbances over the tropical South Atlantic in CMIP6 models - Lucas C. V. Cavalcante; Helber B. Gomes; Kevin Hodges; Pallav Ray; Dirceu L. Herdies; Henrique M. J. Barbosa; Weber A. Gonçalves; Maria Cristina L. Silva; José Ivaldo B. de Brito; João Pedro G. Nobre; Matheus J. A. Lyra; Hakki Baltaci (Climate Dynamics, 2025)

Comparison of Landsat-8 and Sentinel-2 Imagery for Modeling Gross Primary Productivity of Tea Ecosystem - Ali Raza; Yongguang Hu; Yongzong Lu; Ram L. Ray (Journal of Crop Health, 2024)

Exploring the unique biophysical characteristics and ecosystem services of mountains: A review - Gebrekidan Worku Tefera; Ram L. Ray; Amare Bantider (Journal of Mountain Science, 2024)

Intra-neighborhood associations between residential greenness and blood pressure - Ray Yeager; Rachel J. Keith; Daniel W. Riggs; Daniel Fleischer; Matthew H.E.M. Browning; Alessandro Ossola; Kandi L. Walker; Joy L. Hart; Sanjay Srivastava; Shesh N. Rai; Ted Smith; Aruni Bhatnagar (Science of The Total Environment, 2024)

Trends in Arctic-nesting loon (Gavia spp.) populations in North America - Ingrid L. Pollet; Sarah E. Gutowsky; Ray T. Alisauskas; William Harvey; Dana K. Kellett; Kristen M. Lalla; Josée Lefebvre; Jake Russell-Mercier; Jennifer F. Provencher; Emily D. Silverman; Paul A. Smith; Mark L. Mallory (Polar Biology, 2024)

Efficacy of trapping protocols for Agrilus jewel beetles: a multi-country assessment - Giacomo Santoiemma; David Williams; Everett G. Booth; Giacomo Cavaletto; James Connell; Gianfranco Curletti; Maarten de Groot; Sarah M. Devine; Abigail Enston; Joseph A. Francese; Emily K. L. Franzen; Mischa Giasson; et al. (Journal of Pest Science, 2024)
The genus Agrilus is one of the most diverse insect genera worldwide. The larval feeding activity causes extensive damage in both forests and orchards. In addition, more than 30 species have been introduced outside their native range so far, including the emerald ash borer Agrilus planipennis Fairmaire. Thus, the availability of efficient trapping protocols for early detection of Agrilus species at entry points is of utmost importance. In this study we tested whether trapping protocols developed for surveillance of A. planipennis in North America were also effective for other Agrilus species. In particular, through a multi-country assessment we compared the efficacy of detecting Agrilus species on: (i) green glue-coated prism traps vs. green Fluon-coated multi-funnel traps when baited with the green leaf volatile ( Z )-3-hexenol or left unbaited; and (ii) green multi-panel traps vs. green multi-panel traps baited with dead adult Agrilus beetles (decoys). A total of 23,481 individuals from 45 Agrilus species were caught. Trap design significantly affected both species richness and abundance of Agrilus species in several of the countries where the trapping experiments were carried out, and green prism traps outperformed green multi-funnel traps in most cases. On the contrary, the addition of a ( Z )-3-hexenol lure or dead adult beetle decoys on to traps did not improve trap catches. Our study highlights that reliable trap models to survey Agrilus species are already available, but also that there is the clear need to further investigate chemical ecology of Agrilus species to develop semiochemical lures that can improve detection efficacy.

Iron-containing nanominerals for sustainable phosphate management: A comprehensive review and future perspectives - Teng Bao; Mekdimu Mezemir Damtie; Chu Yan Wang; Cheng Long Li; Zhijie Chen; Kuk CHO; Wei Wei; Peng Yuan; Ray L. Frost; Bing-Jie Ni (Science of The Total Environment, 2024)

Consumer preferences for foods with varying best if used-by dates: An experimental auction and sensory evaluation analysis - Billie Ray; Karen L. DeLong; Kimberly Jensen; Sara Burns; Curtis Luckett (Food Policy, 2024)

Comprehensive review of modified clay minerals for phosphate management and future prospects - Teng Bao; Mekdimu Mezemir Damtie; Chu yan Wang; Zhijie Chen; Qi Tao; Wei Wei; Kuk Cho; Peng Yuan; Ray L. Frost; Bing-Jie Ni (Journal of Cleaner Production, 2024)

Effect of dietary phytase on water and fecal prokaryotic and eukaryotic microbiomes in a hybrid tilapia (Oreochromis aureus x O. niloticus) mixotrophic biofloc production system - Candis L. Ray; Jason W. Abernathy; Bartholomew W. Green; Adam R. Rivers; Kevin K. Schrader; Steven D. Rawles; Matthew E. McEntire; Miles D. Lange; Carl D. Webster (Aquaculture, 2024)

HydroShare retrospective: Science and technology advances of a comprehensive data and model publication environment for the water science domain - David G. Tarboton; Daniel P. Ames; Jeffery S. Horsburgh; Jonathan L. Goodall; Alva Couch; Richard Hooper; Jerad Bales; Shaowen Wang; Anthony Castronova; Martin Seul; Ray Idaszak; Zhiyu Li; et al. (Environmental Modelling & Software, 2024)

Hierarchical bimetallic metal-organic frameworks with controllable assembling sub-units and interior architectures for enhanced ammonia detection - Silvia Chowdhury; Nagy L. Torad; Manjeet Godara; Ahmed A.M. El-Amir; Gilang Gumilar; Aditya Ashok; Mohammad Rezaul Karim; Ibrahim Abdullah Alnaser; Watcharop Chaikittisilp; Nirat Ray; Yusuke Yamauchi; Yusuf Valentino Kaneti (Chemical Engineering Journal, 2024)

Electroplating wastewater treatment by in-situ formation of organic anions and inorganic anions intercalated layered double hydroxides - Xiuxiu Ruan; Wangkai Zhu; Zili Jiang; Jianwei Zuo; Ray L. Frost; Godwin A. Ayoko; Guangren Qian (Chemosphere, 2023)

Farm impacts of the 2019 Missouri River floods and economic valuation of flood risk reduction - Theodoros Skevas; Ray Massey; Sherry L. Hunt (Journal of Environmental Management, 2023)

Modelling reference evapotranspiration using principal component analysis and machine learning methods under different climatic environments - Ali Raza; Kouadri Saber; Yongguang Hu; Ram L. Ray; Yunus Ziya Kaya; Hossein Dehghanisanij; Ozgur Kisi; Ahmed Elbeltagi (Irrigation and Drainage, 2023)
Reference evapotranspiration (ET o ) is a complex process in the hydrologic cycle that influences several hydrologic parameters. Although several methods have been developed to model ET o , a reliable method that can use limited climatic input parameters for data‐limited regions is still limited. This study evaluated four machine learning (ML) methods: M5 pruned (M5P) tree, sequential minimal optimization (SMO), radial basis function neural regression (RBFNreg) and multilinear regression (MLR). The major objective of this study was to identify the best approach to estimate ET o with minimum input data in five stations (Multan, Jacobabad, Faisalabad, Islamabad and Skardu) located in Pakistan. The datasets of these stations comprised maximum and minimum temperatures ( T max , T min ), average relative humidity (RH avg ), average wind speed ( U x), and sunshine hours ( n ) variables. Two scenarios were used for ET o modelling. In the first scenario, five climatic variables were used as inputs to estimate ET o as obtaining full climatic parameters is the biggest challenge in developing countries. Principal component analysis (PCA) was used as a clustering technique in the second scenario to reduce the climatic input parameters. The PCA results indicated that T max , T min and n were identified as effective inputs for ET o estimation. Based on statistical indicators, the M5P tree outperformed the other applied ML methods in estimating ET o under various climatic environments. This study recommends focusing on areas with high ET o values and adequate irrigation scheduling of crops to achieve water sustainability.

Porewater and solid phase speciation geochemistry of phosphorus in the Western Bay of Bengal: An assessment of depositional pathways - P. Linsy; B. Nagender Nath; M.B.L. Mascarenhas-Pereira; Tyson Sebastian; B. Ramalingeswara Rao; Armoury Kazip; Durbar Ray; Saranya Jayachandran; L. Surya Prakash (Marine Geology, 2023)

A modified critical load assessment method of heavy metals in paddy soil at large scale - Kongqiu Liang; Junwei Zhong; Wanfu Zhao; Yinxian Song; He Chang; Shitao Zhang; Zhong Chen; Weiwei Zhou; Junfeng Ji; Godwin A. Ayoko; Ray L. Frost; Salim Belyazid (Journal of Cleaner Production, 2023)

The Ontology of Biological Attributes (OBA)—computational traits for the life sciences - Ray Stefancsik; James P. Balhoff; Meghan A. Balk; Robyn L. Ball; Susan M. Bello; Anita R. Caron; Elissa J. Chesler; Vinicius de Souza; Sarah Gehrke; Melissa Haendel; Laura W. Harris; Nomi L. Harris; et al. (Mammalian Genome, 2023)
Existing phenotype ontologies were originally developed to represent phenotypes that manifest as a character state in relation to a wild-type or other reference. However, these do not include the phenotypic trait or attribute categories required for the annotation of genome-wide association studies (GWAS), Quantitative Trait Loci (QTL) mappings or any population-focussed measurable trait data. The integration of trait and biological attribute information with an ever increasing body of chemical, environmental and biological data greatly facilitates computational analyses and it is also highly relevant to biomedical and clinical applications. The Ontology of Biological Attributes (OBA) is a formalised, species-independent collection of interoperable phenotypic trait categories that is intended to fulfil a data integration role. OBA is a standardised representational framework for observable attributes that are characteristics of biological entities, organisms, or parts of organisms. OBA has a modular design which provides several benefits for users and data integrators, including an automated and meaningful classification of trait terms computed on the basis of logical inferences drawn from domain-specific ontologies for cells, anatomical and other relevant entities. The logical axioms in OBA also provide a previously missing bridge that can computationally link Mendelian phenotypes with GWAS and quantitative traits. The term components in OBA provide semantic links and enable knowledge and data integration across specialised research community boundaries, thereby breaking silos.

Environmental implication of geochemical record in the Arctic Ny-Ålesund glacial sediment, Svalbard (Norway) - Yanpeng Yang; Zhong Chen; Yinxian Song; Ming Yan; Chuandong Xue; Junfeng Ji; Godwin A. Ayoko; Ray L. Frost (Science of The Total Environment, 2023)

Cenozoic upper mantle flow history of the Atlantic realm based on Couette/Poiseuille models: Towards paleo-mantle-flowgraphy - Zhirui Ray Wang; Ingo L. Stotz; Hans-Peter Bunge; Berta Vilacís; Jorge N. Hayek; Sia Ghelichkhan; Sergei Lebedev (Physics of the Earth and Planetary Interiors, 2023)

Impact of relative humidity and temperature oscillations mimicking authentic storage during shipping on whey proteins powders properties - J. Burgain; G. Francius; L. Cvetkovska; C. Paris; M. Alexander; C. Ray; S. El-Kirat-Chatel; C. Gaiani (Food Structure, 2023)

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

Mineralogy and geochemistry of hydrothermal sulphide from a submarine volcanic high at 18°36.4′S Central Lau Spreading Center, Southwest Pacific - Durbar Ray; Anil L. Paropkari (Acta Oceanologica Sinica, 2023)

Microbathymetry inferences from two AUV dives over a short segment of the Central Indian Ridge between 10°18′ and 10°57′S, Indian Ocean - K. A. Kamesh Raju; V. Yatheesh; A. Srinivas Rao; L. Surya Prakash; Durbar Ray; Abhay Mudholkar; Kiranmai Samudrala; Nico Augustin; P. John Kurian (Geo-Marine Letters, 2023)

Self-replicating murine ex vivo cultured alveolar macrophages as a model for toxicological studies of particle-induced inflammation - Rebekah L. Kendall; Jessica L. Ray; Raymond F. Hamilton; Andrij Holian (Toxicology and Applied Pharmacology, 2023)

A Meta-Analysis of the Genome-Wide Association Studies on Two Genetically Correlated Phenotypes Suggests Four New Risk Loci for Headaches - Weihua Meng; Parminder S. Reel; Charvi Nangia; Aravind Lathika Rajendrakumar; Harry L. Hebert; Qian Guo; Mark J. Adams; Hua Zheng; Zen Haut Lu; Debashree Ray; Lesley A. Colvin; Colin N. A. Palmer; et al. (Phenomics, 2023)
Headache is one of the commonest complaints that doctors need to address in clinical settings. The genetic mechanisms of different types of headache are not well understood while it has been suggested that self-reported headache and self-reported migraine were genetically correlated. In this study, we performed a meta-analysis of genome-wide association studies (GWAS) on the self-reported headache phenotype from the UK Biobank and the self-reported migraine phenotype from the 23andMe using the Unified Score-based Association Test (metaUSAT) software for genetically correlated phenotypes ( N = 397,385). We identified 38 loci for headaches, of which 34 loci have been reported before and four loci were newly suggested. The LDL receptor related protein 1 ( LRP1 )— Signal Transducer and Activator of Transcription 6 ( STAT6 )— S hort chain D ehydrogenase / R eductase family 9C member 7 ( SDR9C7 ) region in chromosome 12 was the most significantly associated locus with a leading p value of 1.24 × 10 –62 of rs11172113. The One Cut homeobox 2 ( ONECUT2 ) gene locus in chromosome 18 was the strongest signal among the four new loci with a p value of 1.29 × 10 –9 of rs673939. Our study demonstrated that the genetically correlated phenotypes of self-reported headache and self-reported migraine can be meta-analysed together in theory and in practice to boost study power to identify more variants for headaches. This study has paved way for a large GWAS meta-analysis involving cohorts of different while genetically correlated headache phenotypes.

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Wave setup at the Minamitorishima tide gauge - Richard D. Ray; Mark A. Merrifield; Philip L. Woodworth (Journal of Oceanography, 2023)

Assessment of extreme rainfall through statistical process control-I chart - N S Abeysingha; K M Kularathna; A M K R Bandara; Ram L Ray (Journal of Earth System Science, 2023)

Sustainable Growing Areas for Sugarcane in Sri Lanka Under a Changing Climate - D. M. B. M. Deegala; N. S. Abeysingha; L. P. Muthuwatta; Ram L. Ray (Sugar Tech, 2022)

Recent trends in abundance and fishing pressure of agency‐assessed small pelagic fish stocks - Ray Hilborn; Claudio C. Buratti; Erich Díaz Acuña; Daniel Hively; Jeppe Kolding; Hiroyuki Kurota; Nicole Baker; Pamela M. Mace; Carryn L. de Moor; Soyoka Muko; Giacomo Chato Osio; Ana M. Parma; et al. (Fish and Fisheries, 2022)
Small pelagic fishes are used for human consumption, fishmeal and fish oil. They constitute 25% of global fish catch and have been of considerable conservation concern because of their intermediate position in aquatic food webs, often being a dominant dietary component of marine predators. This paper provides an overview of trends in abundance and fishing pressure on small pelagic fish stocks from single‐species scientific assessments that constitute 60% of global small pelagic catch. While most individual stocks have exhibited wide variability in abundance (typical of small pelagics compared with other fish taxa), across stocks there has been remarkable stability in average fishing pressure and biomass since 1970. On average, since 1970, the biomass of assessed small pelagic stocks is estimated to have been slightly above the biomass that would produce maximum sustainable yield, but estimation of this quantity for highly fluctuating stocks is quite uncertain. There were significant differences among assessed regions, with the Mediterranean and Black Sea of greatest concern for high and growing fishing pressure. The 40% of global small pelagic fish catch not covered by single‐species quantitative stock assessments since 1970 comes largely from Asia, where catches have continued to increase. At regional levels, the average abundance of assessed small pelagic fish is largely unrelated to average fishing pressure, which we argue results both from the portfolio effect, where numerous stocks fluctuate with little correlation in abundance, and from the short life span of small pelagics coupled with recruitment largely independent of spawning abundance.

HPV Vaccine Intent among Adult Women Receiving Care at Community Health Centers - M. L. Hecht; R. BeLue; A. Ray; S. Hopfer; M. Miller-Day; F. Mckee (Journal of Cancer Education, 2022)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Variation in migration behaviors used by Arctic Terns (Sterna paradisaea) breeding across a wide latitudinal gradient - Joanna B. Wong; Simeon Lisovski; Ray T. Alisauskas; Willow English; Autumn-Lynn Harrison; Dana K. Kellett; Mark Maftei; Avery Nagy-MacArthur; Robert A. Ronconi; Paul A. Smith; Mark L. Mallory; Marie Auger-Méthé (Polar Biology, 2022)

Testing the potential contribution of Wolbachia to speciation when cytoplasmic incompatibility becomes associated with host‐related reproductive isolation - Daniel J. Bruzzese; Hannes Schuler; Thomas M. Wolfe; Mary M. Glover; Joseph V. Mastroni; Meredith M. Doellman; Cheyenne Tait; Wee L. Yee; Juan Rull; Martin Aluja; Glen Ray Hood; Robert B. Goughnour; et al. (Molecular Ecology, 2022)
Endosymbiont‐induced cytoplasmic incompatibility (CI) may play an important role in arthropod speciation. However, whether CI consistently becomes associated or coupled with other host‐related forms of reproductive isolation (RI) to impede the transfer of endosymbionts between hybridizing populations and further the divergence process remains an open question. Here, we show that varying degrees of pre‐ and postmating RI exist among allopatric populations of two interbreeding cherry‐infesting tephritid fruit flies ( Rhagoletis cingulata and R . indifferens ) across North America. These flies display allochronic and sexual isolation among populations, as well as unidirectional reductions in egg hatch in hybrid crosses involving southwestern USA males. All populations are infected by a Wolbachia strain, w Cin2, whereas a second strain, w Cin3, only co‐infects flies from the southwest USA and Mexico. Strain w Cin3 is associated with a unique mitochondrial DNA haplotype and unidirectional postmating RI, implicating the strain as the cause of CI. When coupled with nonendosymbiont RI barriers, we estimate the strength of CI associated with w Cin3 would not prevent the strain from introgressing from infected southwestern to uninfected populations elsewhere in the USA if populations were to come into secondary contact and hybridize. In contrast, cytoplasmic–nuclear coupling may impede the transfer of w Cin3 if Mexican and USA populations were to come into contact. We discuss our results in the context of the general paucity of examples demonstrating stable Wolbachia hybrid zones and whether the spread of Wolbachia among taxa can be constrained in natural hybrid zones long enough for the endosymbiont to participate in speciation.

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Seasonal variations in the water quality and antibiotic resistance of microbial pollution indicators in the Mandovi and Zuari estuaries, Goa, India - Ashwini D. Toraskar; Cathrine S. Manohar; Charmaine L. Fernandes; Durbar Ray; Abigayle D. Gomes; Ajit Antony (Environmental Monitoring and Assessment, 2022)

Deep‐sea wooden shipwrecks influence sediment microbiome diversity - Justyna J. Hampel; Rachel D. Moseley; Rachel L. Mugge; Anirban Ray; Melanie Damour; Douglas Jones; Leila J. Hamdan (Limnology and Oceanography, 2022)
Historic shipwrecks function as habitats for benthic organisms by providing food, refuge, and structure. They also form islands of biodiversity on the seabed, shaping microbial ecology and ecosystem processes. This study examined two wooden deep‐sea shipwrecks at 525 and 1800 m water depth and probed their influence on sediment microbiomes and geochemistry. Microbiomes were investigated with 16S rRNA gene amplicon sequencing along 60 m transects extending in four directions from the hulls of the shipwrecks. Distance from shipwrecks and sediment depth both shaped microbiome structure. Archaeal alpha diversity was significantly and positively correlated with proximity to the deeper shipwreck while bacterial diversity was not to either. Archaeal community structure differed at both sites; the deeper site had a higher proportion of Bathyarchaeia and Lokiarchaeia proximate to shipwreck compared to the shallow location. Major bacterial communities were consistent at both sites, however, at the deeper site had higher abundance of Bacteroidetes, Chloroflexi, Desulfofarculales, and Desulfobacteriales. Core microbiome and differential abundance analyses revealed unique taxa nearest the shipwrecks compared to the surrounding seabed including organoheterotrophs, and cellulolytic and sulfur cycling taxa. Sediment carbon content influenced microbiome structure near the shipwrecks (5–10 m). We show that shipwrecks have a distinct sediment microbiome and form unique habitat patches on seabed, resembling those surrounding organic falls. The shipwreck influence was more pronounced at the deeper site, further from terrestrial influences signaling shipwrecks may be a significant source of organic matter in far‐shore oligotrophic settings.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Breeding latitude is associated with the timing of nesting and migration around the annual calendar among Purple Martin (Progne subis) populations - L. R. Neufeld; S. Muthukumarana; J. D. Fischer; J. D. Ray; J. Siegrist; K. C. Fraser (Journal of Ornithology, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Global status of groundfish stocks - Ray Hilborn; Daniel J. Hively; Nicole Baker Loke; Carryn L. de Moor; Hiroyuki Kurota; Johannes N. Kathena; Pamela M. Mace; Cóilín Minto; Ana M. Parma; Juan‐Carlos Quiroz; Michael C. Melnychuk (Fish and Fisheries, 2021)
We review the status of groundfish stocks using published scientific assessments for 349 individual stocks constituting 90% of global groundfish catch. Overall, average stock abundance is increasing and is currently above the level that would produce maximum sustainable yield (MSY). Fishing pressure for cod‐like fishes (Gadiformes) and flatfishes (Pleuronectiformes) was, for several decades, on average well above levels associated with MSY, but is now at or below the level expected to produce MSY. In contrast, fishing pressure for rockfishes (Scorpaeniformes) decreased from near MSY‐related levels in the mid‐1990s, and since the mid‐2000s has remained on average at only one third of MSY‐related levels. Regions with the most depressed groundfish stocks are the Northwest Atlantic and the Pacific coast of South America, while stocks from the Northeast and Eastern Central Pacific, Northeast Atlantic, Southeast Atlantic and Southwest Pacific tend to have greatest average abundance relative to MSY‐based reference points. In the most recent year available for each stock, the catch was only 61% of MSY. Equilibrium yield curves indicate that 76% of global potential groundfish yield could be achieved using current estimates of fishing pressure. 15% of this is lost by excess fishing pressure, 67% results from lower than optimal fishing pressure on healthy stocks and 18% is lost from stocks currently overfished but rebuilding. Thus, there is modest opportunity to increase catch of global groundfish fisheries by reducing overfishing on some stocks, but more by increasing harvest on others. However, there may be other reasons not to fully exploit these stocks.

Preface: Developments in the science and history of tides - Philip L. Woodworth; J. A. Mattias Green; Richard D. Ray; John M. Huthnance (Ocean Science, 2021)
This special issue marks the 100th anniversary of the founding of the Liverpool Tidal Institute (LTI), one of a number of important scientific developments in 1919. The preface gives a brief history of how the LTI came about and the roles of its first two directors, Joseph Proudman and Arthur Doodson. It also gives a short overview of the research on tides at the LTI through the years. Summaries are given of the 26 papers in the special issue. It will be seen that the topics of many of them could be thought of as providing a continuation of the research first undertaken at the LTI. Altogether, they provide an interesting snapshot of work on tides now being made by groups around the world.

Was historical cisco Coregonus artedi yield consistent with contemporary recruitment and abundance in Lake Superior? - Benjamin J. Rook; Michael J. Hansen; Cory A. Goldsworthy; Bradley A. Ray; Owen T. Gorman; Daniel L. Yule; Charles R. Bronte (Fisheries Management and Ecology, 2021)
Historically, cisco Coregonus artedi Lesueur was the predominant prey fish and target of commercial fisheries throughout Lake Superior, but most spawning stocks collapsed by the mid‐1900s. Stocks partially recovered by the early 1990s, but contemporary abundance is considered to be below historical levels and driven by intermittent recruitment. Stochastic, age‐structured simulation models were used to determine whether historical (pre‐1955) cisco yield in Lake Superior was consistent with contemporary (1992–2015) abundance, life‐history characteristics and recruitment dynamics. When compared to contemporary stocks, the findings suggest historical stocks had: (1) similar recruits per spawner at low spawning stock sizes; (2) lower rates of compensatory density dependence; (3) similar or lower recruitment variation depending on the area and (4) higher median adult and age‐1 density. These findings are consistent with the hypothesis that eutrophication during the historical period supported greater recruitment and adult abundance and that re‐oligotrophication during the contemporary period may be limiting full recovery.

Impact of an SGLT2-loss of function mutation on renal architecture, histology, and glucose homeostasis - Corey B. Hughes; George M. Mussman; Phil Ray; Robert C. Bunn; Virgilius Cornea; Kathryn M. Thrailkill; John L. Fowlkes; Iuliana Popescu (Cell and Tissue Research, 2021)

Assessment of groundwater depletion–induced land subsidence and characterisation of damaging cracks on houses: a case study in Mohali-Chandigarh area, India - Neha Kadiyan; R. S. Chatterjee; Pranshu Pranjal; Pankaj Agrawal; S. K. Jain; M. L. Angurala; A. K. Biyani; M. S. Sati; Dheeraj Kumar; Ashutosh Bhardwaj; P. K. Champati Ray (Bulletin of Engineering Geology and the Environment, 2021)

β-Adrenoceptor blockade prevents carotid body hyperactivity and elevated vascular sympathetic nerve density induced by chronic intermittent hypoxia - Abdulaziz A. Alzahrani; Lily L. Cao; Hayyaf S. Aldossary; Demitris Nathanael; Jiarong Fu; Clare J. Ray; Keith L. Brain; Prem Kumar; Andrew M. Coney; Andrew P. Holmes (Pflügers Archiv - European Journal of Physiology, 2021)
Carotid body (CB) hyperactivity promotes hypertension in response to chronic intermittent hypoxia (CIH). The plasma concentration of adrenaline is reported to be elevated in CIH and our previous work suggests that adrenaline directly activates the CB. However, a role for chronic adrenergic stimulation in mediating CB hyperactivity is currently unknown. This study evaluated whether beta-blocker treatment with propranolol (Prop) prevented the development of CB hyperactivity, vascular sympathetic nerve growth and hypertension caused by CIH. Adult male Wistar rats were assigned into 1 of 4 groups: Control (N), N + Prop, CIH and CIH + Prop. The CIH paradigm consisted of 8 cycles h −1 , 8 h day −1 , for 3 weeks. Propranolol was administered via drinking water to achieve a dose of 40 mg kg −1 day −1 . Immunohistochemistry revealed the presence of both β 1 and β 2 -adrenoceptor subtypes on the CB type I cell. CIH caused a 2–3-fold elevation in basal CB single-fibre chemoafferent activity and this was prevented by chronic propranolol treatment. Chemoafferent responses to hypoxia and mitochondrial inhibitors were attenuated by propranolol, an effect that was greater in CIH animals. Propranolol decreased respiratory frequency in normoxia and hypoxia in N and CIH. Propranolol also abolished the CIH mediated increase in vascular sympathetic nerve density. Arterial blood pressure was reduced in propranolol groups during hypoxia. Propranolol exaggerated the fall in blood pressure in most (6/7) CIH animals during hypoxia, suggestive of reduced sympathetic tone. These findings therefore identify new roles for β-adrenergic stimulation in evoking CB hyperactivity, sympathetic vascular hyperinnervation and altered blood pressure control in response to CIH.

Cell-Permeable Calpain Inhibitor SJA6017 Provides Functional Protection to Spinal Motoneurons Exposed to MPP+ - Supriti Samantaray; Varduhi H. Knaryan; Angelo M. Del Re; John J. Woodward; Donald C. Shields; Mitsuyoshi Azuma; Jun Inoue; Swapan K. Ray; Naren L. Banik (Neurotoxicity Research, 2020)

Elevated turbidity and dissolved manganese in deep water column near 10°47’S Central Indian Ridge: studies on hydrothermal activities - Durbar Ray; K. A. KameshRaju; A. Srinivas Rao; L. SuryaPrakash; Abhay V. Mudholkar; V. Yatheesh; Kiranmai Samudrala; Dalayya Kota (Geo-Marine Letters, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Cancer mortality risk, fine particulate air pollution, and smoking in a large, representative cohort of US adults - Nathan C. Coleman; Richard T. Burnett; Joshua D. Higbee; Jacob S. Lefler; Ray M. Merrill; Majid Ezzati; Julian D. Marshall; Sun-Young Kim; Matthew Bechle; Allen L. Robinson; C. Arden Pope (Cancer Causes & Control, 2020)

John Leonard Bannister 1937–2018 - Robert L. Brownell; Doug S. Butterworth; Catherine M. Kemper; Martin Cawthorn; Michael Double; Greg P. Donovan; Ray Gambell; Hidehiro Kato (Marine Mammal Science, 2020)

Electric Pulse Pretreatment for Enhanced Lipid Recovery from Chlorella protothecoides - Caleb H. Geissler; Mary L. Mulligan; Zane E. Zmola; Shaunak Ray; John A Morgan; Allen L. Garner (BioEnergy Research, 2020)

Correction to: Development and Utility of an ELISA Method for Sensitive and Specific Detection of IgE Antidrug Antibodies - Lynn L. Jiang; Puneet Khandelwal; Adam W. Clarke; Ray Bakhtiar; Linglong Zou; Zhandong Don Zhong (The AAPS Journal, 2020)

Development and Utility of an ELISA Method for Sensitive and Specific Detection of IgE Antidrug Antibodies - Zhandong Don Zhong; Lynn L. Jiang; Puneet Khandelwal; Adam W. Clarke; Ray Bakhtiar; Linglong Zou (The AAPS Journal, 2020)

Asymmetry in Herbivore Effector Responses: Caterpillar Frass Effectors Reduce Performance of a Subsequent Herbivore - Swayamjit Ray; Anjel M. Helms; Nina L. Matulis; Elizabeth Davidson-Lowe; William Grisales; Jared G. Ali (Journal of Chemical Ecology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Geophagy among East African Chimpanzees: consumed soils provide protection from plant secondary compounds and bioavailable iron - Paula A. Pebsworth; Stephen Hillier; Renate Wendler; Ray Glahn; Chieu Anh Kim Ta; John T. Arnason; Sera L. Young (Environmental Geochemistry and Health, 2019)

Enhanced Production of Shigella flexneri Polysaccharide from a Newly Devised Silicate Method as a Potential Vaccine Conjugate - P. V. S. L. S. S. Narayana; Jayati Ray Dutta (Current Microbiology, 2019)

Forcing Factors Affecting Sea Level Changes at the Coast - Philip L. Woodworth; Angélique Melet; Marta Marcos; Richard D. Ray; Guy Wöppelmann; Yoshi N. Sasaki; Mauro Cirano; Angela Hibbert; John M. Huthnance; Sebastià Monserrat; Mark A. Merrifield (Surveys in Geophysics, 2019)

CO2 uptake and chlorophyll a fluorescence of Suaeda fruticosa grown under diurnal rhythm and after transfer to continuous dark - Silas Wungrampha; Rohit Joshi; Ray S. Rathore; Sneh L. Singla-Pareek; Govindjee; Ashwani Pareek (Photosynthesis Research, 2019)

Unrecognized and imperilled diversity in an endemic barb (Smiliogastrini, Enteromius ) from the Fouta Djallon highlands - Ray C. Schmidt; Megan N. Dillon; Natalie M. Kuhn; Henry L. Bart; Frank Pezold (Zoologica Scripta, 2019)
The Upper Guinean Forests of Guinea, Sierra Leone and Liberia contain high levels of freshwater biodiversity. The Guinean Range and associated Fouta Djallon highlands separate two biogeographical provinces in the region and served as a refugium during past climatic fluctuations. While many species of freshwater fishes are restricted to one biogeographical province or the other, some are reported to occur on both sides of the divide. Here, we examine the molecular and morphological diversity of an endemic small African barb, Enteromius foutensis , reported to occur in both provinces. This integrative analysis revealed unrecognized diversity and suggests recent, or ongoing, events that facilitated geodispersal and subsequent divergence in the region. The molecular analysis revealed three divergent and well‐supported populations within E. foutensis . Accounting for allometric shape variation allowed us to observe diagnostic morphological differences among the populations. Enteromius foutensis sensu stricto is restricted to the Little Scarcies drainage in Guinea and northern Sierra Leone. Our study revealed two candidate species distinct from E. foutensis . One is likely a narrow endemic restricted to a small area in the Konkouré River basin; the other candidate species inhabits the upper Senegal and Gambie River drainages. How these patterns of diversity compare with other freshwater species from the Fouta Djallon highlands and the conservation status of these candidate species are also discussed.

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

The effects of a conventional feed versus a fish-free feed and biofloc management on the nutritional and human sensory characteristics of shrimp (Litopenaeus vannamei) - Andrew J. Ray; John W. Leffler; Craig L. Browdy (Aquaculture International, 2019)

Adsorption of cadmium ions by cucumber peel in continuous mode - M. Basu; A. K. Guha; L. Ray (International Journal of Environmental Science and Technology, 2019)

Assessing the spatiotemporal distributions of evapotranspiration in the Three Gorges Reservoir Region of China using remote sensing data - Ze-zhong Ma; Ram L Ray; Yi-ping He (Journal of Mountain Science, 2018)

Antennal Olfactory Physiology and Behavior of Males of the Ponerine Ant Harpegnathos saltator - Majid Ghaninia; Shelley L. Berger; Danny Reinberg; Laurence J. Zwiebel; Anandasankar Ray; Jürgen Liebig (Journal of Chemical Ecology, 2018)

Coated-Platelet Trends Predict Short-Term Clinical OutcomeAfter Subarachnoid Hemorrhage - Bappaditya Ray; Vijay M. Pandav; Eleanor A. Mathews; David M. Thompson; Lance Ford; Lori K. Yearout; Bradley N. Bohnstedt; Shuchi Chaudhary; George L. Dale; Calin I. Prodan (Translational Stroke Research, 2018)

A review of regulations and guidelines related to winter manure application - Jian Liu; Peter J. A. Kleinman; Helena Aronsson; Don Flaten; Richard W. McDowell; Marianne Bechmann; Douglas B. Beegle; Timothy P. Robinson; Ray B. Bryant; Hongbin Liu; Andrew N. Sharpley; Tamie L. Veith (Ambio, 2018)

Modeling regional landslide susceptibility using dynamic soil moisture profiles - Ram L. Ray; Jennifer M. Jacobs; Ellen M. Douglas (Journal of Mountain Science, 2018)

Response of benthic fauna to experimental bottom fishing: A global meta‐analysis - Marija Sciberras; Jan Geert Hiddink; Simon Jennings; Claire L Szostek; Kathryn M Hughes; Brian Kneafsey; Leo J Clarke; Nick Ellis; Adriaan D Rijnsdorp; Robert A McConnaughey; Ray Hilborn; Jeremy S Collie; et al. (Fish and Fisheries, 2018)
Bottom‐contact fishing gears are globally the most widespread anthropogenic sources of direct disturbance to the seabed and associated biota. Managing these fishing disturbances requires quantification of gear impacts on biota and the rate of recovery following disturbance. We undertook a systematic review and meta‐analysis of 122 experiments on the effects‐of‐bottom fishing to quantify the removal of benthos in the path of the fishing gear and to estimate rates of recovery following disturbance. A gear pass reduced benthic invertebrate abundance by 26% and species richness by 19%. The effect was strongly gear‐specific, with gears that penetrate deeper into the sediment having a significantly larger impact than those that penetrate less. Sediment composition (% mud and presence of biogenic habitat) and the history of fishing disturbance prior to an experimental fishing event were also important predictors of depletion, with communities in areas that were not previously fished, predominantly muddy or biogenic habitats being more strongly affected by fishing. Sessile and low mobility biota with longer life‐spans such as sponges, soft corals and bivalves took much longer to recover after fishing (>3 year) than mobile biota with shorter life‐spans such as polychaetes and malacostracans (

Mineralogical and geochemical variation in hydrothermal sulfides from Vienna Woods field, Manus Basin, Papua New Guinea: constraints on their evolution - Durbar Ray; Ranadip Banerjee; Aninda Mazumder; Anil L. Paropkari; Subir Mukhopadhyay; Srinivasan Balakrishnan (Acta Oceanologica Sinica, 2018)

Incorporating field wind data to improve crop evapotranspiration parameterization in heterogeneous regions - Ray G. Anderson; Jorge F. S. Ferreira; Dennise L. Jenkins; Nildo da Silva Dias; Donald L. Suarez (Irrigation Science, 2017)

S- and Sr-isotopic compositions in barite–silica chimney from the Franklin Seamount, Woodlark Basin, Papua New Guinea: constraints on genesis and temporal variability of hydrothermal fluid - Durbar Ray; Ranadip Banerjee; S. Balakrishnan; Anil L. Paropkari; Subir Mukhopadhyay (International Journal of Earth Sciences, 2017)

Migratory stopover timing is predicted by breeding latitude, not habitat quality, in a long-distance migratory songbird - A. Van Loon; J. D. Ray; A. Savage; J. Mejeur; L. Moscar; M. Pearson; M. Pearman; G. T. Hvenegaard; N. Mickle; K. Applegate; K. C. Fraser (Journal of Ornithology, 2017)

Effect of water on the fluorine and chlorine partitioning behavior between olivine and silicate melt - Bastian Joachim; André Stechern; Thomas Ludwig; Jürgen Konzett; Alison Pawley; Lorraine Ruzié-Hamilton; Patricia L. Clay; Ray Burgess; Christopher J. Ballentine (Contributions to Mineralogy and Petrology, 2017)

A LC-MS/MS Method for Quantifying Adenosine, Guanosine and Inosine Nucleotides in Human Cells - Leah C. Jimmerson; Lane R. Bushman; Michelle L. Ray; Peter L. Anderson; Jennifer J. Kiser (Pharmaceutical Research, 2017)

Corrigendum - Sneha L. Koneru; Heilly Salinas; Gilberto E. Flores; Ray L. Hong (Molecular Ecology, 2016)

Metabarcoding and metabolome analyses of copepod grazing reveal feeding preference and linkage to metabolite classes in dynamic microbial plankton communities - Jessica L. Ray; Julia Althammer; Katrine S. Skaar; Paolo Simonelli; Aud Larsen; Diane Stoecker; Andrey Sazhin; Umer Z. Ijaz; Christopher Quince; Jens C. Nejstgaard; Marc Frischer; Georg Pohnert; et al. (Molecular Ecology, 2016)
In order to characterize copepod feeding in relation to microbial plankton community dynamics, we combined metabarcoding and metabolome analyses during a 22‐day seawater mesocosm experiment. Nutrient amendment of mesocosms promoted the development of haptophyte ( Phaeocystis pouchetii )‐ and diatom ( Skeletonema marinoi )‐dominated plankton communities in mesocosms, in which Calanus sp. copepods were incubated for 24 h in flow‐through chambers to allow access to prey particles ( P. pouchetii , were passively consumed or even negatively selected according to our indicator. Our analysis of the relationship between Calanus grazing ratios and intracellular metabolite profiles indicates the importance of carbohydrates and lipids in plankton succession and copepod–prey interactions. This molecular characterization of Calanus sp. grazing therefore provides new evidence for selective feeding in mixed plankton assemblages and corroborates previous findings that copepod grazing may be coupled to the developmental and metabolic stage of the entire prey community rather than to individual prey abundances.

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Development and validation of cross-transferable and polymorphic DNA markers for detecting alien genome introgression in Oryza sativa from Oryza brachyantha - Soham Ray; Lotan K. Bose; Joshitha Ray; Umakanta Ngangkham; Jawahar L. Katara; Sanghamitra Samantaray; Lambodar Behera; Mahender Anumalla; Onkar N. Singh; Meingsheng Chen; Rod A. Wing; Trilochan Mohapatra (Molecular Genetics and Genomics, 2016)

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

Soybean Aphid Response to their Alarm Pheromone E-ß-Farnesene (EBF) - Jaclyn L. Eichele; Jamin Dreyer; Ray Heinz; Stephen P. Foster; Deirdre A. Prischmann-Voldseth; Jason P. Harmon (Journal of Insect Behavior, 2016)

Sub-Lethal Effects of Copper on Salmonids: An Avoidance Evaluation Using a Direct Test Method - Eric L. Van Genderen; Diana L. Dishman; W. Ray Arnold; Joseph W. Gorsuch; Daniel J. Call (Bulletin of Environmental Contamination and Toxicology, 2016)

Neuron specific enolase: a promising therapeutic target in acute spinal cord injury - Azizul Haque; Swapan K. Ray; April Cox; Naren L. Banik (Metabolic Brain Disease, 2016)

The bacterial community of entomophilic nematodes and host beetles - Sneha L. Koneru; Heilly Salinas; Gilberto E. Flores; Ray L. Hong (Molecular Ecology, 2016)
Insects form the most species‐rich lineage of Eukaryotes and each is a potential host for organisms from multiple phyla, including fungi, protozoa, mites, bacteria and nematodes. In particular, beetles are known to be associated with distinct bacterial communities and entomophilic nematodes. While entomopathogenic nematodes require symbiotic bacteria to kill and reproduce inside their insect hosts, the microbial ecology that facilitates other types of nematode–insect associations is largely unknown. To illuminate detailed patterns of the tritrophic beetle–nematode–bacteria relationship, we surveyed the nematode infestation profiles of scarab beetles in the greater Los Angeles area over a five‐year period and found distinct nematode infestation patterns for certain beetle hosts. Over a single season, we characterized the bacterial communities of beetles and their associated nematodes using high‐throughput sequencing of the 16S rRNA gene. We found significant differences in bacterial community composition among the five prevalent beetle host species, independent of geographical origin. Anaerobes Synergistaceae and sulphate‐reducing Desulfovibrionaceae were most abundant in Amblonoxia beetles, while Enterobacteriaceae and Lachnospiraceae were common in Cyclocephala beetles. Unlike entomopathogenic nematodes that carry bacterial symbionts, insect‐associated nematodes do not alter the beetles' native bacterial communities, nor do their microbiomes differ according to nematode or beetle host species. The conservation of Diplogastrid nematodes associations with Melolonthinae beetles and sulphate‐reducing bacteria suggests a possible link between beetle–bacterial communities and their associated nematodes. Our results establish a starting point towards understanding the dynamic interactions between soil macroinvertebrates and their microbiota in a highly accessible urban environment.

New climate change information modifies frames and decisions of decision makers: an exploratory study in forest planning - Michal Petr; L. G. J. Boerboom; Duncan Ray; Anne van der Veen (Regional Environmental Change, 2016)

SEM, EDX and vibrational spectroscopic study of the carbonate mineral donnayite-(Y) NaCaSr3Y(CO3)6·3H2O - Ray L. Frost; Andrés López; Ricardo Scholz; Bárbara Firmino (Carbonates and Evaporites, 2016)

Outdoor Water Use as an Adaptation Problem: Insights from North American Cities - Patricia Gober; Ray Quay; Kelli L. Larson (Water Resources Management, 2016)

Real‐time spatial management approaches to reduce bycatch and discards: experiences from Europe and the United States - Alyson S Little; Coby L Needle; Ray Hilborn; Daniel S Holland; C Tara Marshall (Fish and Fisheries, 2015)
Spatial management measures are currently being used to manage bycatch and discards, given the spatial heterogeneity of fish distributions. However, permanent fishing closures are often poorly implemented, unresponsive to stock dynamics and do not achieve their management objectives. Recently, real‐time spatial management tools for managing bycatch and discards implemented under either a comanagement or self‐governance approach have been introduced in Europe and the US . Real‐time catch and discard information is shared among fishers to incentivise and encourage vessels to leave areas of high bycatch. Here, the similarities and differences, in governance, implementation and management of ten real‐time spatial management systems from across Europe and the US are reviewed. A framework is developed to characterize the attributes associated with voluntary, private and regulatory real‐time spatial management tools. Challenges and management practices in the different case studies are reviewed providing insights for designing these spatial management tools. The results illustrate that real‐time spatial management approaches can create incentives for fishers to develop, use and share information and technology to avoid undesired catch. Compared with Europe, the US has developed spatial management tools with more truly real‐time mechanisms and with greater involvement of the fishing industry in designing and operating the tools.

Peter B. Best (1939–2015) - John Bannister; Ken Findlay; Robert L. Brownell; Doug Butterworth; Martin Cawthorn; Greg Donovan; Ray Gambell; Hidehiro Kato; Bruce Mate; Michael Moore; Seiji Ohsumi; William Perrin; et al. (Marine Mammal Science, 2015)

Norwegian deep‐water coral reefs: cultivation and molecular analysis of planktonic microbial communities - Sigmund Jensen; Michael D. J. Lynch; Jessica L. Ray; Josh D. Neufeld; Martin Hovland (Environmental Microbiology, 2015)
Summary Deep‐sea coral reefs do not receive sunlight and depend on plankton. Little is known about the plankton composition at such reefs, even though they constitute habitats for many invertebrates and fish. We investigated plankton communities from three reefs at 260–350 m depth at hydrocarbon fields off the mid‐ N orwegian coast using a combination of cultivation and small subunit ( SSU ) rRNA gene and transcript sequencing. Eight months incubations of a reef water sample with minimal medium, supplemented with carbon dioxide and gaseous alkanes at in situ ‐like conditions, enabled isolation of mostly A lphaproteobacteria ( S ulfitobacter , L oktanella ) , G ammaproteobacteria ( C olwellia ) and F lavobacteria ( P olaribacter ). The relative abundance of isolates in the original sample ranged from ∼ 0.01% to 0.80%. Comparisons of bacterial SSU sequences from filtered plankton of reef and non‐reef control samples indicated high abundance and metabolic activity of primarily A lphaproteobacteria ( SAR 11 Ia), G ammaproteobacteria ( ARCTIC 96 BD ‐19), but also of D eltaproteobacteria ( N itrospina , SAR 324). Eukaryote SSU sequences indicated metabolically active microalgae and animals, including codfish, at the reef sites. The plankton community composition varied between reefs and differed between DNA and RNA assessments. Over 5000 operational taxonomic units were detected, some indicators of reef sites (e.g. F lavobacteria , C ercozoa , D emospongiae ) and some more active at reef sites (e.g. G ammaproteobacteria , C iliophora , C opepoda ).

Habitat Characteristics and Their Effects on the Density of Groups of Western Hoolock Gibbon (Hoolock hoolock) in Namdapha National Park, Arunachal Pradesh, India - Parimal Chandra Ray; Awadhesh Kumar; Ashalata Devi; Murali C. Krishna; M. L. Khan; W. Y. Brockelman (International Journal of Primatology, 2015)

A review of iron species for visible-light photocatalytic water purification - Russell S. Jack; Godwin A. Ayoko; Moses O. Adebajo; Ray L. Frost (Environmental Science and Pollution Research, 2015)

Determinants of summer weather extremes over the Canadian prairies: implications for long-lead grain forecasting - E. Ray Garnett; Madhav L. Khandekar (Natural Hazards, 2015)

Small-scale variability in water storage and plant available water in shallow, rocky soils - Ieyasu Tokumoto; James L. Heilman; Susanne Schwinning; Kevin J. McInnes; Marcy E. Litvak; Cristine L. S. Morgan; Ray H. Kamps (Plant and Soil, 2014)

Trading in snails: plant nurseries as transport hubs for non-native species - Elizabeth A. Bergey; Laura L. Figueroa; Charles M. Mather; Rebekah J. Martin; Eric J. Ray; Jobin T. Kurien; David R. Westrop; Phushewan Suriyawong (Biological Invasions, 2014)

Greenhouse gases generated from the anaerobic biodegradation of natural offshore asphalt seepages in southern California - Thomas D. Lorenson; Florence L. Wong; Peter Dartnell; Ray W. Sliter (Geo-Marine Letters, 2014)

Vibrational spectroscopy of the borate mineral olshanskyite Ca3[B(OH)4]4(OH)2 - Ray L. Frost; Yunfei Xi; Ricardo Scholz; Matheus da Costa Alves Pereira (Carbonates and Evaporites, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Targeting oncogenic ALK and MET: a promising therapeutic strategy for glioblastoma - Gerald C. Wallace; Yaenette N. Dixon-Mah; W. Alex Vandergrift; Swapan K. Ray; Catherine P. Haar; Amber M. Mittendorf; Sunil J. Patel; Naren L. Banik; Pierre Giglio; Arabinda Das (Metabolic Brain Disease, 2013)

Sequential hTERT Knockdown and Apigenin Treatment Inhibited Invasion and Proliferation and Induced Apoptosis in Human Malignant Neuroblastoma SK-N-DZ and SK-N-BE2 Cells - Mrinmay Chakrabarti; Naren L. Banik; Swapan K. Ray (Journal of Molecular Neuroscience, 2013)

Reproductive factors and risk of lung cancer in female textile workers in Shanghai, China - Lisa G. Gallagher; Karin A. Rosenblatt; Roberta M. Ray; Wenjin Li; Dao L. Gao; Katie M. Applebaum; Harvey Checkoway; David B. Thomas (Cancer Causes & Control, 2013)

Effect of Age and Exercise on the Viscoelastic Properties of Rat Tail Tendon - Andrew S. LaCroix; Sarah E. Duenwald-Kuehl; Stacey Brickson; Tiffany L. Akins; Gary Diffee; Judd Aiken; Ray Vanderby; Roderic S. Lakes (Annals of Biomedical Engineering, 2013)

Historical thermal regimes define limits to coral acclimatization - Emily J. Howells; Ray Berkelmans; Madeleine J. H. van Oppen; Bette L. Willis; Line K. Bay (Ecology, 2013)
Knowledge of the degree to which corals undergo physiological acclimatization or genetic adaptation in response to changes in their thermal environment is crucial to the success of coral reef conservation strategies. The potential of corals to acclimatize to temperatures exceeding historical thermal regimes was investigated by reciprocal transplantation of Acropora millepora colonies between the warm central and cool southern regions of the Great Barrier Reef (GBR) for a duration of 14 months. Colony fragments retained at native sites remained healthy, whereas transplanted fragments, although healthy over initial months when temperatures remained within native thermal regimes, subsequently bleached and suffered mortality during seasonal temperature extremes. Corals hosting Symbiodinium D transplanted to the southern GBR bleached in winter and the majority suffered whole (40%; n = 20 colonies) or partial (50%) mortality at temperatures 1.1°C below their 15‐year native minimum. In contrast, corals hosting Symbiodinium C2 transplanted to the central GBR bleached in summer and suffered whole (50%; n = 10 colonies) or partial (42%) mortality at temperatures 2.5°C above their 15‐year native maximum. During summer bleaching, the dominant Symbiodinium type changed from C2 to D within corals transplanted to the central GBR. Corals transplanted to the cooler, southern GBR grew 74–80% slower than corals at their native site, and only 50% of surviving colonies reproduced, at least partially because of cold water bleaching of transplants. Despite the absence of any visual signs of stress, corals transplanted to the warmer, central GBR grew 52–59% more slowly than corals at their native site before the summer bleaching (i.e., from autumn to spring). Allocation of energy to initial acclimatization or reproduction may explain this pattern, as the majority (65%) of transplants reproduced one month earlier than portions of the same colonies retained at the southern native site. All parameters investigated (bleaching, mortality, Symbiodinium type fidelity, reproductive timing) demonstrated strong interactions between genotype and environment, indicating that the acclimatization potential of A. millepora populations may be limited by adaptation of the holobiont to native thermal regimes.

Asynchronous food‐web pathways could buffer the response of Serengeti predators to El Niño Southern Oscillation - A. R. E. Sinclair; Kristine L. Metzger; John M. Fryxell; Craig Packer; Andrea E. Byrom; Meggan E. Craft; Katie Hampson; Tiziana Lembo; Sarah M. Durant; Guy J. Forrester; John Bukombe; John Mchetto; et al. (Ecology, 2013)
Understanding how entire ecosystems maintain stability in the face of climatic and human disturbance is one of the most fundamental challenges in ecology. Theory suggests that a crucial factor determining the degree of ecosystem stability is simply the degree of synchrony with which different species in ecological food webs respond to environmental stochasticity. Ecosystems in which all food‐web pathways are affected similarly by external disturbance should amplify variability in top carnivore abundance over time due to population interactions, whereas ecosystems in which a large fraction of pathways are nonresponsive or even inversely responsive to external disturbance will have more constant levels of abundance at upper trophic levels. To test the mechanism underlying this hypothesis, we used over half a century of demographic data for multiple species in the Serengeti (Tanzania) ecosystem to measure the degree of synchrony to variation imposed by an external environmental driver, the El Niño Southern Oscillation (ENSO). ENSO effects were mediated largely via changes in dry‐season vs. wet‐season rainfall and consequent changes in vegetation availability, propagating via bottom‐up effects to higher levels of the Serengeti food web to influence herbivores, predators and parasites. Some species in the Serengeti food web responded to the influence of ENSO in opposite ways, whereas other species were insensitive to variation in ENSO. Although far from conclusive, our results suggest that a diffuse mixture of herbivore responses could help buffer top carnivores, such as Serengeti lions, from variability in climate. Future global climate changes that favor some pathways over others, however, could alter the effectiveness of such processes in the future.

Chemistry, Raman and infrared spectroscopic characterization of the phosphate mineral reddingite: (MnFe)3(PO4)2(H2O,OH)3, a mineral found in lithium-bearing pegmatite - Ray L. Frost; Yunfei Xi; Ricardo Scholz; Fernanda M. Belotti; Leonardo E. Lagoeiro (Physics and Chemistry of Minerals, 2012)

2,3-Hexanediols as Sex Attractants and a Female-produced Sex Pheromone for Cerambycid Beetles in the Prionine Genus Tragosoma - Ann M. Ray; James D. Barbour; J. Steven McElfresh; Jardel A. Moreira; Ian Swift; Ian M. Wright; Alenka Žunič; Robert F. Mitchell; Elizabeth E. Graham; Ronald L. Alten; Jocelyn G. Millar; Lawrence M. Hanks (Journal of Chemical Ecology, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Sulphide production and corrosion in seawaters during exposure to FAME diesel - Jason S. Lee; Richard I. Ray; Brenda J. Little; Kathleen E. Duncan; Athenia L. Oldham; Irene A. Davidova; Joseph M. Suflita (Biofouling, 2012)

Movement and persistence by Ross’s Geese (Chen rossii) in Canada’s arctic - Ray T. Alisauskas; Kiel L. Drake; Jason H. Caswell; Dana K. Kellett (Journal of Ornithology, 2012)

(R)-Desmolactone, A Female-produced Sex Pheromone Component of the Cerambycid Beetle Desmocerus californicus californicus (subfamily Lepturinae) - Ann M. Ray; Ian P. Swift; J. Steven McElfresh; Ronald L. Alten; Jocelyn G. Millar (Journal of Chemical Ecology, 2012)

Regional landslide susceptibility: spatiotemporal variations under dynamic soil moisture conditions - Ram L. Ray; Jennifer M. Jacobs; Thomas P. Ballestero (Natural Hazards, 2011)

Lung myeloid-derived suppressor cells and regulation of inflammation - Prabir Ray; Meenakshi Arora; Stephanie L. Poe; Anuradha Ray (Immunologic Research, 2011)

Pathogenic Botryosphaeriaceae associated with Mangifera indica in the Kimberley Region of Western Australia - Monique L. Sakalidis; Jane D. Ray; Vincent Lanoiselet; Giles E. StJ. Hardy; Treena I. Burgess (European Journal of Plant Pathology, 2011)

Multiple tracers demonstrate distinct sources of dissolved organic matter to lakes of the Mackenzie Delta, western Canadian Arctic - Suzanne E. Tank; Lance F. W. Lesack; Jolie A. L. Gareis; Christopher L. Osburn; Ray H. Hesslein (Limnology and Oceanography, 2011)
Lakes of the Mackenzie Delta occur across a gradient that contains three clear end members: those that remain connected to river‐water channels throughout the summer; those that receive only brief inputs of river water during an annual spring flood but contain dense macrophyte stands; and those that experience significant permafrost thaw along their margins. We measured dissolved organic carbon (DOC) concentration, dissolved organic matter (DOM) absorption and fluorescence, and stable isotopes of DOM, DOM precursor materials, and bacteria to elucidate the importance of river water, macrophytes, and thermokarst as DOM sources to Mackenzie Delta lakes. Despite standing stocks of macrophyte C that are sevenfold to 12‐fold greater than those of total DOC, stable isotopes indicated that autochthonous sources contributed less than 15% to overall DOM in macrophyte‐rich lakes. Instead, fluorescence and absorption indicated that the moderate summertime increase in DOC concentration in macrophyte‐rich lakes was the result of infrequent flushing, while bacterial δ 13 C indicated rapid bacterial removal of autochthonous DOC from the water column. In thermokarst lakes, summertime increases in DOC concentration were substantial, and stable isotopes indicated that much of this increase came from C released as a result of thermokarst‐related processes. Our results indicate that these distinct sources of DOM to neighboring arctic Delta lakes may drive between‐lake differences in C cycling and energy flow. Rapidly assimilated macrophyte DOM should be an important contributor to microbial food webs in our study lakes. In contrast, the accumulation of thermokarst‐origin DOM allows for a significant role in physico‐chemistry but indicates a lesser contribution of this DOM to higher trophic levels.

Glucosinolate content and nematicidal activity of Brazilian wild mustard tissues against Meloidogyne incognita in tomato - Rosângela D. L. Oliveira; Onkar D. Dhingra; André O. Lima; Gulab N. Jham; Mark A. Berhow; Ray K. Holloway; Steven F. Vaughn (Plant and Soil, 2011)

Deriving biomedical diagnostics from NMR spectroscopic data - Ian C. P. Smith; Ray L. Somorjai (Biophysical Reviews, 2011)

cis-Vaccenyl Acetate, A Female-Produced Sex Pheromone Component of Ortholeptura valida, A Longhorned Beetle in the Subfamily Lepturinae - Ann M. Ray; Alenka Žunič; Ronald L. Alten; J. Steven McElfresh; Lawrence M. Hanks; Jocelyn G. Millar (Journal of Chemical Ecology, 2011)

Role of the atmospheric mean state on the initiation of the Madden-Julian oscillation in a tropical channel model - Pallav Ray; Chidong Zhang; Mitchell W. Moncrieff; Jim Dudhia; Julie M. Caron; L. Ruby Leung; Cindy Bruyere (Climate Dynamics, 2011)

Development and characterization of 16 microsatellite markers for the Louisiana pine snake, Pituophis ruthveni, and two congeners of conservation concern - Matthew A. Kwiatkowski; Christopher M. Somers; Ray G. Poulin; D. Craig Rudolph; Jessica Martino; Tracey D. Tuberville; Cris Hagen; Stacey L. Lance (Conservation Genetics Resources, 2010)

Evaluating the protection of wildlife in parks: the case of African buffalo in Serengeti - K. L. Metzger; A. R. E. Sinclair; Ray Hilborn; J. Grant C. Hopcraft; Simon A. R. Mduma (Biodiversity and Conservation, 2010)

Hypoxia Inducible Factor-1α (HIF-1α) and Some HIF-1 Target Genes are Elevated in Experimental Glaucoma - Ceren Ergorul; Arjun Ray; Wei Huang; Dan Yi Wang; Yixin Ben; Ippolita Cantuti-Castelvetri; Cynthia L. Grosskreutz (Journal of Molecular Neuroscience, 2010)

Rebound Discharge in Deep Cerebellar Nuclear Neurons In Vitro - Reza Tadayonnejad; Dustin Anderson; Michael L. Molineux; W. Hamish Mehaffey; Kusala Jayasuriya; Ray W. Turner (The Cerebellum, 2010)

Trusting Emergence: Some Experiences of Learning about Integrated Catchment Science with the Environment Agency of England and Wales - Kevin B. Collins; Ray L. Ison (Water Resources Management, 2010)

Molecular detection of genomic regions associated with grain yield and yield-related components in an elite bread wheat cross evaluated under irrigated and rainfed conditions - C. Lynne McIntyre; Ky L. Mathews; Allan Rattey; Scott C. Chapman; Janneke Drenth; Mohammadghader Ghaderi; Matthew Reynolds; Ray Shorter (Theoretical and Applied Genetics, 2010)

Crop sequence as a tool for managing populations of Fusarium pseudograminearum and F. culmorum in south-eastern Australia - Margaret L. Evans; Grant J. Hollaway; Jeremy I. Dennis; Ray Correll; Hugh Wallwork (Australasian Plant Pathology, 2010)

High-Oil Soybean for More Efficient Energy Conversion to Soy-Based Biodiesel - Robert L. Paris; Jeffery D. Ray; James R. Smith; Debbie L. Boykin (Natural Resources Research, 2009)

Late Pleistocene to Holocene sedimentation and hydrocarbon seeps on the continental shelf of a steep, tectonically active margin, southern California, USA - Amy E. Draut; Patrick E. Hart; Thomas D. Lorenson; Holly F. Ryan; Florence L. Wong; Ray W. Sliter; James E. Conrad (Marine Geophysical Research, 2009)

Hippuric acid and benzoic acid inhibition of urine derived N 2 O emissions from soil - JANET E. BERTRAM; TIM J. CLOUGH; ROBERT R. SHERLOCK; LEO M. CONDRON; MAUREEN O'CALLAGHAN; NAOMI S. WELLS; JESSICA L. RAY (Global Change Biology, 2009)
Atmospheric concentrations of the greenhouse gas nitrous oxide (N 2 O) have continued to rise since the advent of the industrial era, largely because of the increase in agricultural land use. The urine deposited by grazing ruminant animals is a major global source of agricultural N 2 O. With the first commitment period for reducing greenhouse gas emissions under the Kyoto Protocol now underway, mitigation options for ruminant urine N 2 O emissions are urgently needed. Recent studies showed that increasing the urinary concentration of the minor urine constituent hippuric acid resulted in reduced emissions of N 2 O from a sandy soil treated with synthetic bovine urine, due to a reduction in denitrification. A similar effect was seen when benzoic acid, a product of hippuric acid hydrolysis, was used. This current laboratory experiment aimed to investigate these effects using real cow urine for the first time. Increased concentrations of hippuric acid or benzoic acid in the urine led to reduction of N 2 O emissions by 65% (from 17% to 2 O fluxes. This study indicates the potential for developing a novel mitigation strategy based on manipulation of urine composition through ruminant diet.

Global GPS data analysis at the National Geodetic Survey - William G. Kass; Robert L. Dulaney; Jake Griffiths; Stephen Hilla; Jim Ray; James Rohde (Journal of Geodesy, 2009)

Oral contraceptives and the risk of all cancers combined and site-specific cancers in Shanghai - Karin A. Rosenblatt; Dao L. Gao; Roberta M. Ray; Zakia C. Nelson; Karen J. Wernli; Wenjin Li; David B. Thomas (Cancer Causes & Control, 2009)

Characterization of Insertion Sites in Rainbow Papaya, the First Commercialized Transgenic Fruit Crop - Jon Y. Suzuki; Savarni Tripathi; Gustavo A. Fermín; Fuh-Jyh Jan; Shaobin Hou; Jimmy H. Saw; Christine M. Ackerman; Qingyi Yu; Michael C. Schatz; Karen Y. Pitz; Marcela Yépes; Maureen M. M. Fitch; et al. (Tropical Plant Biology, 2008)

Genome-Wide Analysis of Repetitive Elements in Papaya - Niranjan Nagarajan; Rafael Navajas-Pérez; Mihai Pop; Maqsudul Alam; Ray Ming; Andrew H. Paterson; Steven L. Salzberg (Tropical Plant Biology, 2008)

Multi-environment QTL mixed models for drought stress adaptation in wheat - Ky L. Mathews; Marcos Malosetti; Scott Chapman; Lynne McIntyre; Matthew Reynolds; Ray Shorter; Fred van Eeuwijk (Theoretical and Applied Genetics, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Soybean molecular linkage group B1 corresponds to classical linkage group 16 based on map location of the lf 2 gene - Thomas M. Seversike; Jeffery D. Ray; Jeffry L. Shultz; Larry C. Purcell (Theoretical and Applied Genetics, 2008)

Sex hormone binding globulin in breast cancer - Dayalu Naik S L; Suresh Hedau; Anil Kumar Bahadur; Renuka Saha; Sudershan Kaur; Amitabha Ray (Indian Journal of Clinical Biochemistry, 2008)

Characterization of periodic variations in the GPS satellite clocks - Kenneth L. Senior; Jim R. Ray; Ronald L. Beard (GPS Solutions, 2008)

Age and microvascular responses to knee extensor exercise in women - Beth A. Parker; Sandra L. Smithmyer; Samuel J. Ridout; Chester A. Ray; David N. Proctor (European Journal of Applied Physiology, 2008)

Bioaccumulation of Heavy Metals by Green Algae - Hiren Doshi; Chetan Seth; Arabinda Ray; I. L. Kothari (Current Microbiology, 2008)

History repeated: recent and historical mitochondrial introgression between the current darter Etheostoma uniporum and rainbow darter Etheostoma caeruleum (Teleostei: Percidae) - J. M. Ray; N. J. Lang; R. M. Wood; R. L. Mayden (Journal of Fish Biology, 2008)
Incongruence between recognized taxonomy and phylogenetic relationships between two species from a diverse clade (Percidae: Etheostomatinae) of stream fishes was found in a mitochondrial (mt) DNA gene tree. Two darters in subgenus Oligocephalus , Etheostoma uniporum current darter and Etheostoma caeruleum rainbow darter were sampled throughout their sympatric distribution in the Ozark Highlands of the central United States. Sequences from cytochrome (cyt) b and the first intron of the nuclear marker S7 were analysed separately using maximum parsimony and Bayesian methods. Cyt b recovered both species as polyphyletic; E. uniporum haplotypes were interspersed within E. caeruleum . However, both species were monophyletic and non‐sister taxa based on S7. The cyt b gene tree pattern is caused by introgressive hybridization resulting in the mtDNA replacement of E. uniporum haplotypes by those of E. caeruleum . Some E. uniporum haplotypes are shared with geographically proximate E. caeruleum , and this is consistent with recent hybridization, while other E. uniporum haplotypes indicate historical sorting of introgressed lineages. The mechanism of introgression is likely asymmetric sneaking behaviour by male E. uniporum , a mating tactic observed in related species. MtDNA replacement may have occurred in E. uniporum due to drift fixation in a historically small female effective population. Additional evidence for darter hybridization will likely be discovered in future molecular genetic surveys of the nearly 200 species in eastern North America.

Relationships among remotely sensed soil moisture, precipitation and landslide events - Ram L. Ray; Jennifer M. Jacobs (Natural Hazards, 2007)

Combination of all-trans retinoic acid and taxol regressed glioblastoma T98G xenografts in nude mice - Surajit Karmakar; Naren L. Banik; Sunil J. Patel; Swapan K. Ray (Apoptosis, 2007)

Chromosomal location and gene paucity of the male specific region on papaya Y chromosome - Qingyi Yu; Shaobin Hou; Roman Hobza; F. Alex Feltus; Xiue Wang; Weiwei Jin; Rachel L. Skelton; Andrea Blas; Cornelia Lemke; Jimmy H. Saw; Paul H. Moore; Maqsudul Alam; et al. (Molecular Genetics and Genomics, 2007)

Garlic compounds induced calpain and intrinsic caspase cascade for apoptosis in human malignant neuroblastoma SH-SY5Y cells - Surajit Karmakar; Naren L. Banik; Sunil J. Patel; Swapan K. Ray (Apoptosis, 2007)

Biosorption of Cadmium by Live and Dead Spirulina: IR Spectroscopic, Kinetics, and SEM Studies - Hiren Doshi; Arabinda Ray; I. L. Kothari (Current Microbiology, 2007)

Induced abortions and the risk of all cancers combined and site-specific cancers in Shanghai - Karin A. Rosenblatt; Dao L. Gao; Roberta M. Ray; Michelle R. Rowland; Zakia C. Nelson; Karen J. Wernli; Wenjin Li; David B. Thomas (Cancer Causes & Control, 2006)

Spectroscopic and Scanning Electron Microscopy Studies of Bioaccumulation of Pollutants by Algae - Hiren Doshi; Arabinda Ray; I. L. Kothari; Bharat Gami (Current Microbiology, 2006)

Stellate cell apoptosis by a soluble mediator from immortalized human hepatocytes - Arnab Basu; Kousuke Saito; Keith Meyer; Ratna B. Ray; Scott L. Friedman; Yie-Hwa Chang; Ranjit Ray (Apoptosis, 2006)

Analysis of papaya BAC end sequences reveals first insights into the organization of a fruit tree genome - Chun Wan J. Lai; Qingyi Yu; Shaobin Hou; Rachel L. Skelton; Meghan R. Jones; Kanako L. T. Lewis; Jan Murray; Moriah Eustice; Peizhu Guan; Ricelle Agbayani; Paul H. Moore; Ray Ming; et al. (Molecular Genetics and Genomics, 2006)

Gape Limitation, Prey Size Refuges and the Top–down Impacts of Piscivorous Largemouth Bass in Shallow Pond Ecosystems - Weston H. Nowlin; Ray W. Drenner; Kirk R. Guckenberger; Mark A. Lauden; G. Todd Alonso; Joseph E. Fennell; Judson L. Smith (Hydrobiologia, 2006)

Effect of ascorbic acid on prevention of hypercholesterolemia induced atherosclerosis - S. Das; R. Ray; Snehlata; N. Das; L. M. Srivastava (Molecular and Cellular Biochemistry, 2006)

Reproductive history, occupational exposures, and thyroid cancer risk among women textile workers in Shanghai, China - E. Y. Wong; R. Ray; D. L. Gao; K. J. Wernli; W. Li; E. D. Fitzgibbons; Z. Feng; D. B. Thomas; H. Checkoway (International Archives of Occupational and Environmental Health, 2006)

Colorectal Cancer Incidence Among Female Textile Workers in Shanghai, China: A Case-cohort Analysis of Occupational Exposures - A.J. De Roos; R. M. Ray; D. L. Gao; K. J. Wernli; E. D. Fitzgibbons; F. Ziding; G. Astrakianakis; D. B. Thomas; H. Checkoway (Cancer Causes & Control, 2005)

In Memorium - Douglas Wartzok; Peter L. Tyack; G. Carleton Ray (Marine Mammal Science, 2005)

Decreased apoptosis in polyamine depleted IEC-6 cells depends on Akt-mediated NF-κB activation but not GSK3β activity - S. Bhattacharya; R. M. Ray; L. R. Johnson (Apoptosis, 2005)

The dynamics of landscape change and snow geese in mid‐continent North America - Kenneth F. Abraham; Robert L. Jefferies; Ray T. Alisauskas (Global Change Biology, 2005)
The Mid‐Continent Population of the lesser snow goose, which breeds in the eastern and central Canadian Arctic and sub‐Arctic, and winters in the southern United States and northern Mexico has increased 5–7% annually from the late 1960s to the mid‐1990s, largely because of increased survival in response to an agricultural food subsidy. The rise in numbers complements the increased use of nitrogen fertilizers and a corresponding rise in yields of rice, corn, and wheat along the flyways and on the wintering grounds. In sub‐Arctic migration areas and at Arctic breeding colonies, foraging by high numbers of birds has led to loss of coastal vegetation, adverse changes in soil properties and the establishment of an alternative stable state of exposed sediment, which can be detected with LANDSAT imagery. At a local scale, gosling growth, size and survival decreased in affected areas and other taxa have been adversely affected. The food subsidy on wintering and migration areas appears insufficient to meet reproductive demands as foraging in spring continues to occur on southern Hudson Bay staging and nesting areas. The recent introduction of liberal hunting regulations may reduce population size in the near term, but the revegetation of these coastal ecosystems will take decades to achieve. The present pattern of vegetation loss in these Arctic coastal systems is likely to continue in the forseeable future.

Intra-specific DNA polymorphism in pineapple (Ananas comosus (L.) Merr.) assessed by AFLP markers - Cecilia Y. Kato; Chifumi Nagai; Paul H. Moore; Francis Zee; Minna S. Kim; Denise L. Steiger; Ray Ming (Genetic Resources and Crop Evolution, 2005)

Population-based diallel analyses among nine historically recognized alfalfa germplasms - A. Segovia-Lerma; L. W. Murray; M. S. Townsend; I. M. Ray (Theoretical and Applied Genetics, 2004)

Rapid establishment of fish in isolated peatland beaver ponds - Heather L. Ray; Andrew M. Ray; Alan J. Rebertus (Wetlands, 2004)

Analysis of cropping pattern changes in Bathinda district, Punjab - Sushma Panigrahy; S. S. Ray; Anil Sood; L. B. Patel; P. K. Sharma; J. S. Parihar (Journal of the Indian Society of Remote Sensing, 2004)

Releasing the peri-neuronal net to patch-clamp neurons in adult CNS - Fernando R. Fernandez; Suzanne Sinclair; Michael L. Molineux; W. Hamish Mehaffey; Ray W. Turner; Ezequiel Morales (Pflügers Archiv - European Journal of Physiology, 2004)

A Line 1 insertion in the Factor IX gene segregates with mild hemophilia B in dogs - Marjory B. Brooks; Weikuan Gu; Jennifer L. Barnas; Jharna Ray; Kunal Ray (Mammalian Genome, 2003)

Amino Acid Deamination by Ruminal Megasphaera elsdenii Strains - Jennifer L. Rychlik; Ray LaVera; James B. Russell (Current Microbiology, 2002)

Integrated Two-Dimensional Modeling of Fluid Flow and Compaction in a Sedimentary Basin - Zhangxin Chen; Richard E. Ewing; Hao Lu; Stephen L. Lyons; Serguei Maliassov; Michael B. Ray; Tong Sun (Computational Geosciences, 2002)

Hierarchical habitat selection by barren-ground grizzly bears in the central Canadian Arctic - Philip D. McLoughlin; Ray L. Case; Robert J. Gau; Dean H. Cluff; Robert Mulders; François Messier (Oecologia, 2002)

Assessing the Roles of Patch Quality, Area, and Isolation in Predicting Metapopulation Dynamics - Erica Fleishman; Chris Ray; Per Sjögren‐Gulve; Carol L. Boggs; Dennis D. Murphy (Conservation Biology, 2002)
Two aspects of patch geometry—area and isolation—currently dominate the field of metapopulation dynamics. Under this area‐and‐isolation paradigm, models commonly assume that the probability of local extinction decreases as patch area increases and that the probability of colonization increases as patch connectivity increases. Environmental variables other than patch area and isolation are assumed to have relatively little effect on metapopulation dynamics. Our work on a metapopulation of the butterfly Speyeria nokomis apacheana highlights the need for a broader view of metapopulation dynamics. In this system, neither occupancy nor turnover patterns were best modeled as functions of patch area or isolation. Instead, other measures of habitat quality explained the most variance in occupancy and turnover. Our study also revealed temporal variation in the factors associated with occupancy and turnover. This variation can cause the results of analyses to vary with the temporal scale of analysis. For example, factors associated with turnover in this system differed among single‐year and multiple‐year analyses. We emphasize that factors other than patch geometry may drive extinction and colonization processes in metapopulations, especially in systems that experience substantial natural and anthropogenic environmental variability.

The effect of vapor pressure deficit on maize transpiration response to a drying soil - Jeffery D. Ray; Russ W. Gesch; Thomas R. Sinclair; L. Hartwell Allen (Plant and Soil, 2002)

Tracing the Sources of Exported Nitrate in the Turkey Lakes Watershed Using 15 N/ 14 N and 18 O/ 16 O isotopic ratios - John Spoelstra; Sherry L. Schiff; Richard J. Elgood; Ray G. Semkin; Dean S. Jeffries (Ecosystems, 2001)

Serum oestradiol in women with carcinomas of the breast and uterine cervix - Amitabha Ray; Anil Kumar Bahadur; S. L. Dayalu Naik; Bhuvnesh Kumar Sharma (Indian Journal of Clinical Biochemistry, 2001)

Foraging time and dietary intake by breeding Ross's and Lesser Snow Geese - Mark L. Gloutney; Ray T. Alisauskas; Alan D. Afton; Stuart M. Slattery (Oecologia, 2001)

Serum lipids, lipoproteins and sex-hormone binding globulin in breast cancer - A. Ray; S. L. Dayalu Naik; A. K. Bahadur; S. T. Pasha; R. S. Rautela; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2001)

Status of epidermal growth factor receptors family in hormone-dependent carcinomas of the breast and prostate with reference to serum lipids and lipoproteins - D. Jain; A. Ray; A. K. Bahadur; K. U. Chaturvedi; R. Sood; S. Sharma; S. L. D. Naik; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2001)

Frequency of cytochrome P 450 3A4 variant genotype in transplant population and lack of association with cyclosporin clearance - L. P. Rivory; H. Qin; S. J. Clarke; J. Eris; G. Duggin; E. Ray; R. J. Trent; J. F. Bishop (European Journal of Clinical Pharmacology, 2000)

A rare case of two malignancies: Carcinoma of the breast and uterine cervix - A. Ray; H. Mukundan; A. K. Bahadur; R. S. Rautela; S. L. D. Naik; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2000)

Partitioning linear trends in age-adjusted rates - Benjamin F. Hankey; Lynn A. Ries; Carol L. Kosary; Eric J. Feuer; Ray M. Merrill; Limin X. Clegg; Brenda K. Edwards (Cancer Causes & Control, 2000)

Interactions Between the Atmospheric Sciences and Insurers in the United States - Stanley A. Changnon; E. Ray Fosse; Eugene L. Lecomte (Climatic Change, 1999)

Trichinella spiralis infection in voles alters female odor preference but not partner preference - Sabra L. Klein; H. Ray Gamble; Randy J. Nelson (Behavioral Ecology and Sociobiology, 1999)

Comparison of MPTP-induced changes in spontaneous neuronal discharge in the internal pallidal segment and in the substantia nigra pars reticulata in primates - T. Wichmann; Hagai Bergman; Philip A. Starr; Mahlon R. DeLong; Ray L. Watts; T. Subramanian (Experimental Brain Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Rupestris Stem Pitting Associated Virus-1 is Consistently Detected in Grapevines that are Infected with Rupestris Stem Pitting - Baozhong Meng; Ray Johnson; Silvano Peressini; Philip L. Forsline; Dennis Gonsalves (European Journal of Plant Pathology, 1999)

The role of prostate-specific antigen (PSA) testing patterns in the recent prostate cancer incidence declinein the United States - Julie M. Legler; Eric J. Feuer; Arnold L. Potosky; Ray M. Merrill; Barnett S. Kramer (Cancer Causes & Control, 1998)

High-Level Expression of Ice Nuclei in Erwinia herbicola Is Induced by Phosphate Starvation and Low Temperature - Amy L. Fall; Ray Fall (Current Microbiology, 1998)

Relationships of chestnut species and New Zealand chestnut selections using morpho-nut characters - Nnadozie C. Oraguzie; David L. McNeil; David J. Klinac; Ray D. Knowles; J. Richard Sedcole (Euphytica, 1998)

Tissue-specific activation of the osmotin gene by ABA, C2H4 and NaCl involves the same promoter region - K. G. Raghothama; Albino Maggio; Meena L. Narasimhan; Andrzej K. Kononowicz; Guangli Wang; Matilde Paino D'Urzo; Paul M. Hasegawa; Ray A. Bressan (Plant Molecular Biology, 1997)

Rabies viruses infect primary cultures of murine, feline, and human microglia and astrocytes - N. B. Ray; C. Power; W. P. Lynch; L. C. Ewalt; D. L. Lodmell (Archives of Virology, 1997)

Gonadogenesis, embryogenesis, and unusual oocyte origin in Notogaeanemertes folzae Riser, 1988 (Nemertea, Hoplonemertea) - Frank B. Crandall; Jon L. Norenburg; Ray Gibson (Hydrobiologia, 1997)

Genetic differentiation of populations of the common intertidal nemerteans Lineus ruber and Lineus viridis (Nemertea, Anopla) - Alex D. Rogers; John P. Thorpe; Ray Gibson; Jon L. Norenburg (Hydrobiologia, 1997)

Human bactericidal antibody response to meningococcal outer membrane protein vaccines - W. D. Zollinger; J. Boslego; L. O. Frholm; J. S. Ray; E. E. Moran; B. L. Brandt (Antonie van Leeuwenhoek, 1987)

Chemical and biological characterization of volatile components of environmental samples after fractionation by vacuum line cryogenic distillation - Ray L. Hanson; Alan R. Dahl; Simon J. Rothenberg; Janet M. Benson; Antone L. Brooks; John S. Dutcher (Archives of Environmental Contamination and Toxicology, 1985)

Effects of cadmium on yolk utilization, growth, and survival of Atlantic salmon alevins and newly feeding fry - R. H. Peterson; J. L. Metcalfe; S. Ray (Archives of Environmental Contamination and Toxicology, 1983)

Effects of copper on the sabellid polychaete,Eudistylia vancouveri. II. Copper accumulation and tissue injury in the branchial crown - James S. Young; Roy R. Adee; Irene Piscopo; Ray L. Buschbom (Archives of Environmental Contamination and Toxicology, 1981)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Effects of copper on the sabellid polychaete,Eudistylia vancouveri: I. Concentration limits for copper accumulation - James S. Young; Ray L. Buschbom; James M. Gurtisen; Stephen P. Joyce (Archives of Environmental Contamination and Toxicology, 1979)

Some plant nutrient relationships in the potato crop grown on a calcareous soil - Jay L. Haddock; Ray D. Jackson (American Journal of Potato Research, 1959)

Growth and nutrient uptake of russet burbank potatoes - Ray D. Jackson; Jay L. Haddock (American Journal of Potato Research, 1959)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

Potato notes - J. T. Rosa; C. Tice; A. E. Wilkinson; B. G. Southwick; E. A. Stokdyk; Ray D. Hews; E. L. Newdick; W. Stuart; H. C. Moore; H. O. Werner; J. F. Hockey; C. L. Bailey; et al. (American Journal of Potato Research, 1924)